IFN-γ-driven intratumoral microenvironment exhibits superior prognostic effect compared with an IFN-α-driven microenvironment in patients with colon carcinoma - Grenz, Sandra; Naschberger, Elisabeth; Merkel, Susanne; Britzen-Laurent, Nathalie; Schaal, Ute; Konrad, Andreas; Aigner, Michael; Rau, Tilman; Hartmann, Arndt; Croner, Roland S.; Hohenberger, Werner; Stürzl, Michael (American Journal of Pathology, 2013)
Interferon (IFN)-α and IFN-γ are cytokines with potent immunomodulating and anti-tumor activities. It is unknown which of the two IFNs may be more potent in the regulation of an anti-tumorigenic response in colorectal carcinoma or whether both cytokines cooperate. We, therefore, established human myxovirus resistance protein A and human guanylate-binding protein-1 as markers for the differential detection of IFN-α- and IFN-γ-driven tumor micromilieus, respectively. In vitro studies with different cultures of tumor cells from colorectal carcinoma and stroma cells showed that the expression of myxovirus resistance protein A was exclusively induced by IFN-α, whereas guanylate-binding protein-1 was strongly induced by IFN-γ and only weakly by IFN-α. This expression pattern was used to distinguish cell activation caused by the two cytokines in a clinical cohort of patients with colon carcinoma (n = 378). Patients with primary tumors expressing only guanylate-binding protein-1 exhibited the highest cancer-specific 5-year survival (94.0%, P = 0.006) compared with those expressing both factors (90.3%, P = 0.006), myxovirus resistance protein A alone (83.5%, P = 0.096), or none (72.8%). Our study describes a successful proof-of-principle approach that complex cytokine interaction networks can be dissected in human tissues and demonstrates that an IFN-γ-driven tumor microenvironment exhibits a superior prognostic effect compared with an IFN-α-driven tumor microenvironment in colon carcinoma. © 2013 American Society for Investigative Pathology.
Created from Fastlane, Scopus look-up